REGIONAL FINANCIAL PERFORMANCE OF THE GOVERNMENT OF LEMBATA REGENCY BASED ON THE OPINION OF THE SUPREME AUDIT BOARD - Enike Tje Yustin Dima; Frederic Winston Nalle (SEAN Institute, 2023)
Good and correct regional financial management will greatly affect the presentation of the financial statements and opinions of BPK RI. Therefore the goal to be achieved in this study is to determine the regional financial performance of the Lembata Regency government based on the opinion of the Supreme Audit Agency (BPK) using an analysis of effectiveness ratios, independence ratios, fiscal decentralization ratios, expenditure management ratios , harmony ratios, and growth ratios. . based on timely reporting of financial reports. The type of data used is secondary data from BPK audit reports and financial reports of the Lembata district government for the 2017 to 2021 fiscal year. The results of this study indicate that the financial performance of the Lembata district government in general is still very poor. This is indicated by the high level of fiscal decentralization, the ratio of regional financial independence which is still very low, and the operational expenditure ratio which still dominates the capital expenditure ratio so that it has real implications for the minus value of regional financial performance. growth ratio in the analysis period.